First sightings : contemporary stories of American youth - Loughery, John. (New York : Persea Books, 1993)
Presents twenty short stories, with protagonists aged three to eighteen years old, by such authors as John Updike, Alice Walker, Genaro Gonzales, and Carson McCullers.
Includes bibliographical references (p.289-292)
Keywords: Short stories, American; Short stories